The structure and crystallisation of laser condensates vanadium deposited in oxygen atmosphere - Bagmut, A.G.; Grigorov, S.N.; Zhuchkov, V.A.; Kolosov, V.Yu.; Kosevich, V.M.; Melnichenko, D.V. (Functional Materials, 2006)
The phase composition and structure of films deposited by laser sputtering of V in oxygen atmosphere have been diagnosed by electron diffraction and transmission electron microscopy using "in situ" procedures as well as by consideration of bend extinction contours. It has been shown that at the substrate temperature Ts ranging from 20 to 360°C and the oxygen pressure P(0₂) in the evaporation chamber from 5*10⁻³ to 1.3*10⁻¹ Pa, the oxygen concentration in the film increases as the P(0₂) rises at fixed Ts, while at fixed P(0₂), it decreases as Ts is elevated. The existence areas and compositions of the crystalline (V₀O₃) and amorphous (V₀O₃) phases have been established as well as the fact of the film composition fractionation as a function of the vapor-plasma flow condensation angle. The V₂O₃ spherulites growing in the amorphous phase have distorted (bent) crystal lattice, the bend attaining about 42 deg per μm. The amorphous phase crystallization is accompanied by the density increase by 9.2 %.